Village Financial Management By E-Village Budgeting - Rizal, Chairul; Supiyandi, Supiyandi; Fachri, Barany; Eka, Muhammad; Nasution, Yusuf Ramadhan (International Conference on Sciences Development and Technology, 2022)
Bad governance or poor governance by some economic actors is one of the causes of the economic crisis in Indonesia. So that the emergence of public mistrust of government performance. To restore public confidence to the government, good governance is needed, one of which is the application of e-government. E-government is a form of information and communication technology by the government which can provide information and services to the public, business affairs, and matters relating to government. One of the results of the development of e-government is e-Village Budgeting. E-village budgeting is an online-based village budget management application in order to increase transparency and accountability of the village budget. One of the problems that often arises in the administration of village governance is related to the administrative system of village financial management that is not orderly, so that not a few that cause problems of irregularities in the use of the budget. This research will be designed a web-based application that can help make financial reporting easier. The application was made so that budgeting and development monitoring in remote villages are more transparent.